2020
DOI: 10.1097/jsa.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to Return to Sport After ACL Reconstruction: A Combination of Physical and Psychological Factors

Abstract: Although the incidence of anterior cruciate ligament injuries continues to rise, return to sport (RTS) rates remain low and risk of the second injury remains high. No gold-standard criteria exist for medical clearance to RTS after anterior cruciate ligament reconstruction. The lack of consensus may be driven by the multifactorial nature of the clinical decision that includes a combination of physical and psychological factors. Tools such as the Quality of Movement Assessment, which identifies physical deficits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…49,50 Results following ACL surgery are extremely satisfactory but current evidence suggests that, besides the role of patient's individual risk factors, no specific technique, no graft choice, and no fixation device is able to provide superior outcomes. 51,52 Therefore, biologic augmentation soon came into play: as expected, the literature revealed that PRP-products are the most commonly used in this particular field, due to their easier preparation protocol and lower costs compared to cell-based approaches. A comprehensive analysis of the literature can be appropriately performed if we consider ACL reconstruction and ACL repair separately.…”
Section: Discussionmentioning
confidence: 95%
“…49,50 Results following ACL surgery are extremely satisfactory but current evidence suggests that, besides the role of patient's individual risk factors, no specific technique, no graft choice, and no fixation device is able to provide superior outcomes. 51,52 Therefore, biologic augmentation soon came into play: as expected, the literature revealed that PRP-products are the most commonly used in this particular field, due to their easier preparation protocol and lower costs compared to cell-based approaches. A comprehensive analysis of the literature can be appropriately performed if we consider ACL reconstruction and ACL repair separately.…”
Section: Discussionmentioning
confidence: 95%
“…As the athlete progresses to RTS tasks, biomechanics, neurocognitive training, psychological readiness, and cardiopulmonary conditioning all converge. 103 If any of these factors have not been addressed prior to RTS tasks, they will likely hinder an athlete's ability to return to full activity safely. 104 Repetitive tasks such as walking, biking, and jogging should be seen as opportunities for neuromuscular retraining and neurocognitive training.…”
Section: Nervous System Integration With the Cardiopulmonary Systemmentioning
confidence: 99%
“…[9][10][11]13 At this time, there is a lack of standardized assessment components for return to sport or agreement on the criteria for determining readiness for sport participation. 14 Furthermore, although assessment of psychological readiness for sport has been recommended, 15 it is not performed as frequently. Poor correlation between physical and psychological measures suggests that these are separate factors that cannot be used as surrogates for each other.…”
Section: Introductionmentioning
confidence: 99%